Меню

УСЛОВИЕ:
Представьте выражение в виде степени с основанием 3 и найдите его значение : а) \( 81* 3^{-6} \)
б) \( \frac{ (-3^{-3})^{3} }{ -9^{-2} } \)
в) \( 9^{-5}* ( \frac{1}{9}) ^{-3} \)
г) \( (-3^{-3})^{2}* 27^{3} \)


РЕШЕНИЕ:$$ 1)3^4*3 ^{-6} = ^{-2} =1/9 $$
$$ 2)(-3) ^{-9}/(-3 ^{-4}) =-3 ^{-5} =-1/243 $$
$$ 3) 9^{-5} *9^3=9 ^{-2} =1/81 $$
$$ 4)(-3) ^{-6} *3^9=3^3=27 $$

А)
$$ 81*3^{-6}=3^4*3^{-6}=3^{4+(-6)}=3^{-2}=\frac{1}{9} $$

б)
$$\frac{(-3^{-3})^3}{-9^{-2}}=\frac{-3^{-3*3}}{-(3^2)^{-2}}=\\=\frac{-3^{-9}}{-(3)^{2*(-2)}}=\frac{-3^{-9}}{-(3)^{-4}}=3^{-9-(-4)}=3^{-9+4}=\\=3^{-5}=\frac{1}{243}$$
в)
$$ 9^{-5}*(\frac{1}{9})^{-3}=\\=(3^2)^{-5}*(3^{-2})^{-3}=3^{2*(-5)}*3^{-2*-3}=3^{-10}*3^6=\\=3^{-4}=\frac{1}{81} $$
г)
$$ (-3^{-3})^2*27^3=(-3)^{-3*2}*(3^3)^3=(-3)^{-6}*3^9=(-1*3)^{-6}*3^9=\\=(-1)^{-6}*3^{-6}*3^9=1*3^{-6+9}=3^3=27 $$






Похожие примеры: